2009
DOI: 10.1002/lary.20491
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage grafts in dorsal nasal augmentation of traumatic saddle nose deformity: A long‐term follow‐up

Abstract: Autogenous cartilage grafts are useful in the correction of mild to moderate traumatic saddle nose deformity. The graft is readily available, preserves long-term structural stability, and achieves functional and cosmetic satisfaction in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…A few studies have reported surgical outcomes of saddle nose. In a review of 20 saddle nose cases, Mao et al 13 reported that only 5% had unsuccessful surgical results. There could be several reasons why the surgical results of the study by Mao et al were considerably better than ours.…”
Section: Discussionmentioning
confidence: 98%
“…A few studies have reported surgical outcomes of saddle nose. In a review of 20 saddle nose cases, Mao et al 13 reported that only 5% had unsuccessful surgical results. There could be several reasons why the surgical results of the study by Mao et al were considerably better than ours.…”
Section: Discussionmentioning
confidence: 98%
“…Dorsal augmentation can be used when there is severe injury and deflection, as well as in the weak or cartilage depleted nose. 3 Dorsal augmentation aims to improve the dorsal profile as well as conceal traumatic deformities (►Fig. 8A-C).…”
Section: Dorsal Augmentationmentioning
confidence: 99%
“…These deformities are caused by collapse of the dorsal and/or caudal nasal septum following traumatic septal dislocation from the bony nose due to high-impact trauma or necrosis of the cartilage from septal hematoma nasal. 3 Reconstruction of saddle nose deformities is challenging. It is important to determine the severity of the saddle nose deformity.…”
Section: Dorsal Augmentationmentioning
confidence: 99%
See 2 more Smart Citations